2010
DOI: 10.1016/j.jcrs.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term therapeutic efficacy of phacoemulsification with intraocular lens implantation in patients with phacomorphic glaucoma

Abstract: Phacoemulsification with IOL implantation was effective in treating phacomorphic glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
5
24
0
2
Order By: Relevance
“…[14][15][16][17][18] Several studies have shown that cataract extraction provides the opportunity to restore vision and to eliminate a narrow angle in eyes with acute primary angle-closure or chronic primary angle-closure glaucoma. 6,11,19 Thus, removal of the lens may eliminate an important primary pathology in CACG.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Several studies have shown that cataract extraction provides the opportunity to restore vision and to eliminate a narrow angle in eyes with acute primary angle-closure or chronic primary angle-closure glaucoma. 6,11,19 Thus, removal of the lens may eliminate an important primary pathology in CACG.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5] When the lens swells, angle-closure with pupillary block occurs in the acute phase; in the late phase, it can occur even without pupillary block as a result of forward movement of the peripheral iris. [6][7] However, not all patients with mature cataract inevitably develop phacomorphic angle closure. It is important to identify which of the patients with mature cataract are at increased risk of phacomorphic glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Following IOP stabilisation, cataract extraction was conducted. Phacoemulsification and IOL implantation effectively treat phacomorphic glaucoma with lower complication rates than other cataract extraction procedures; however, regardless of the technique used, cataract surgery in patients with phacomorphic glaucoma carries with it a slightly higher risk than in normal eyes. For example in this patient, the need to dilate the right pupil before surgery increases the risk of another angle closure and her left atonic pupil was difficult to fully dilate, thereby reducing visibility during surgery.…”
Section: Discussionmentioning
confidence: 99%